AN EXPLORATORY ACOUSTIC ANALYSIS OF ENGLISH INTERROGATIVES BY NATIVE DANISH AND INDONESIAN CHINESE MALE SPEAKERS - Tri Utami; Tengku Syarfina (Jurnal Suluh Pendidikan, 2026)
This exploratory study investigates the acoustic realization of English interrogative sentences produced by native Danish and Indonesian Chinese male speakers. The study aims to identify cross-linguistic tendencies in second language (L2) prosody through the analysis of three acoustic parameters: duration, intensity, and pitch. The target sentence “Do you like coffee?” was recorded under controlled conditions and analyzed using Praat software. Although based on a very small sample (two speakers per group), the analysis revealed distinct prosodic tendencies between the two groups. The Danish speakers generally produced shorter utterances with greater pitch and intensity variation, while the Indonesian Chinese speakers tended to produce longer and more uniform duration patterns with narrower pitch ranges. These patterns may reflect influences from each group’s first language rhythmic and tonal systems, though the results remain exploratory and non-generalizable due to the limited data. The findings provide preliminary insights into cross-linguistic tendencies in L2 English interrogative prosody and highlight the need for replication with larger participant groups. Pedagogically, the study underscores the potential relevance of prosody-focused pronunciation instruction for learners from syllable-timed and tonal language backgrounds.